Reconciling Epigenetic Memory and Transcriptional Responsiveness - Fisher,AG; Stumpf,MPH; Merkenschlager,M (CELL SYSTEMS, 2017)
The molecular basis of cellular memory is important but poorly understood. Using estimates of histone dynamics, Martin Howard and colleagues construct a mathematical model that helps to explain both the stability and flexibility of Polycomb-mediated gene regulation in cellular memory.